Assessment of insecticidal treatment combinations in mungbean against thrips and pod borer complex (Journal of the Bangladesh Agricultural University, 2020)
The experiment was conducted at the farmers’ field of Itbaria of Patuakhali sadar upazila under Patuakhali district, Bangladesh during late rabi season in 2018 to find out the suitable insecticidal treatment combinations against thrips and pod borers of mungbean by various treatment combinations, including chemicals, botanicals and biological. Experiment was laid out in a randomized complete block design with five insecticidal treatment combinations and all the combinations were replicated four times. The mungbean variety, BARI Mung-6 was grown in the field and four insecticidal treatment combinations were viz., T1 [Chlorpyrifos + Cypermethrin (Nitro 505EC) + Azadirachtin (Bioneem plus 1EC)], T2 [Thiamethoxam + Chlorantraniliprole (Voliam flexi 300SC) + Azadirachtin (Bioneem plus 1EC)], T3 [Chlorpyrifos + Cypermethrin (Nitro 505EC) + Spinosad (Tracer 45SC)], T4 [Thiamethoxam + Chlorantraniliprole (Voliam flexi 300SC) + Spinosad (Tracer 45SC)] and T0 [Untreated control]. The treatments were applied at reproductive stages of plant. The treatments showed significantly different performance against thrips (Megalurothrips distalis), gram pod borer (Helicoverpa armigera) and legume pod borer (Maruca vitrata) on mungbean. The lowest population of thrips, gram pod borer and legume pod borer was found in T4 treated plot which showed maximum percent reduction of insect pests. The percent pod infestation by pod borers was found lowest in the T4 treatment. The maximum yield (1589.63 kg/ha) and the highest marginal benefit cost ratio (MBCR) (1.60) were also obtained from T4. It can be concluded that T4 was more effective among the insecticidal treatment combinations for controlling thrips and pod borer complex of mungbean which was followed by T2.J Bangladesh Agril Univ 18(2): 300–306, 2020https://doi.org/10.5455/JBAU.84547